Karen's kittycat club - Martin, Ann M., 1955-; Farina, Katy (Baby-sitters little sister (Graphix (Firm)), 2021)
A graphic-novel rendering of the third entry in the Baby-sitters Club spin-off series finds Kristy's younger sister, Karen, trying to form a cat-sitting club with her friends.